Distribution and Drug Resistance of Bacterial Pathogens Associated with Lower Respiratory Tract Infection in Children and the Effect of COVID-19 on the Distribution of Pathogens - Zhu, Xuan; Ye, Ting; Zhong, Hong; Luo, Yaxuan; Xu, Jian; Zhang, Qin; Luo, Xiaobo; Wang, Qin; Zhang, Liyuan; Song, Peipei; Zhang, Jun (The Canadian journal of infectious diseases & medical microbiology, 2022)
By studying the distribution and drug resistance of bacterial pathogens associated with lower respiratory tract infection (LRTI) in children in Chengdu and the effect of the COVID-19 on the distribution of pathogens and by analyzing the epidemic trend and drug resistance changes of the main pathogens of LRTI, this research is supposed to provide a useful basis for the prevention of LRTI in children and the rational use of drugs in clinical practice. Hospitalized children clinically diagnosed with LRTI in Chengdu Women and Children’s Central Hospital from 2011 to 2020 were selected as the study subjects. The pathogens of LRTI in children and the distribution of pathogens in different ages, genders, seasons, years, and departments and before and after the pandemic situation of COVID-19 were counted. The drug resistance distribution of the top six pathogens with the highest infection rate in the past three years and the trend of drug resistance in the past decade were analyzed. A total of 26,469 pathogens were isolated. Among them, 6240 strains (23.6%) were Gram-positive bacteria, 20152 strains (76.1%) were Gram-negative bacteria, and 73 strains (0.3%) were fungi. Klebsiella pneumoniae, Escherichia coli, Enterobacter cloacae, and Staphylococcus aureus were highly isolated in the group of infants aged 0-1 P<0.01, Moraxella catarrhalis and Streptococcus pneumoniae were highly isolated in children aged 1–6 P<0.01, and Haemophilus influenzae was highly isolated in children over 1 P<0.01. The isolation rates of Enterobacteriaceae, Acinetobacter baumannii, Pseudomonas aeruginosa, Stenotrophomonas maltophilia, Staphylococcus aureus, and Candida albicans in the lower respiratory tract of 0-1 year-old male infants were higher than those of female infants p<0.05. Haemophilus influenzae was highly isolated in spring and summer, and Moraxella catarrhalis was highly isolated in autumn and winter, while the infection of Streptococcus pneumoniae was mainly concentrated in winter. This difference was statistically significant P<0.01. Affected by the COVID-19 pandemic, the isolation rates of Haemophilus influenzae and Streptococcus pneumoniae were significantly lower than those before the pandemic, and the isolation rate of Moraxella catarrhalis was significantly higher. The difference was statistically significant P<0.01. The proportion of isolated negative bacteria in NICU and PICU was higher than that in positive bacteria, and the infection rates of Klebsiella pneumoniae, Escherichia coli, Enterobacter cloacae, and Acinetobacter baumannii were higher than those in other departments. The differences were statistically significant P<0.01. The results of drug sensitivity test showed that the drug resistance of Haemophilus influenzae and Moraxella catarrhalis was mainly concentrated in Ampicillin, First- and Second-generation cephalosporins, and Cotrimoxazole, with stable sensitivity to Third-generation cephalosporins, while the drug resistance of Streptococcus pneumoniae was concentrated in Macrolides, Sulfonamides, and Tetracyclines, with stable sensitivity to Penicillin. Staphylococcus aureus is highly resistant to penicillins and macrolides and susceptible to vancomycin. Enterobacteriaceae resistance is concentrated in cephalosporins, with a low rate of carbapenem resistance. From 2018 to 2020, 1557 strains of Staphylococcus aureus were isolated, of which 416 strains were MRSA, accounting for 27% of the isolates; 1064 strains of Escherichia coli were isolated, of which 423 strains were ESBL and 23 strains were CRE, accounting for 40% and 2% of the isolates, respectively; and 1400 strains of Klebsiella pneumoniae were isolated, of which 385 strains were ESBL and 402 strains were CRE, accounting for 28% and 29% of the isolates, respectively. Since 2011, the resistance of Escherichia coli and Klebsiella pneumoniae to Third-generation cephalosporins has increased, peaking in 2017, and has decreased after 2018, years after which carbapenem resistance has increased significantly, corresponding to an increase in the detection rate of Carbapenem-resistant Enterobacteriaceae CRE. Findings from this study revealed that there are significant differences in community-associated infectious pathogens before and after the COVID-19 pandemic, and there are significant age differences, seasonal epidemic trends, and high departmental correlation of pathogens related to lower respiratory tract disease infection in children. There was a significant gender difference in the isolation rate of pathogens associated with LRTI in infants under one year. Vaccination, implementation of isolation measures and social distance, strengthening of personal protective measures, aseptic operation of invasive medical treatment, hand hygiene, and environmental disinfection are beneficial to reducing community-associated pathogen infection, opportunistic pathogen infection, and an increase in resistant bacteria. The strengthening of bacterial culture of lower respiratory tract samples by pediatricians is conducive to the diagnosis of respiratory tract infections caused by different pathogens, contributing to the selection of effective drugs for treatment according to drug susceptibility results, which is important for the rational use of antibiotics and curbing bacterial resistance.